Produksi Pengetahuan dalam Psikologi Berhampiran Budaya - Supratiknya, Augustinus (Fakultas Psikologi Universitas Sanata Dharma, 2024)
The subject matter of the culturally-turned Psychology is subjectivity. Adopting the postructuralist Lacanian theory of subjectivity, the human subject is the split subject and/or the lacking subject. The dinamics of subjectivity are constituted by the Other’s desire that circulates in the daily life in the form of discourse and affects subjectivity through identification and interpellation. Research in the culturally turned Psychology aims at creating or constructing in the sense of producing (new) knowledge through reading or interpreting phenomena including things, actions, social institutions, social events, various forms of speech including written, visual, oral, and the like, all of which may be treated as social texts in the sense of a world of signifiers that represents certain meanings in the widest sense of the word. Such kind of research may be conceived as a form of cultural criticism; hence it should ultimately create difference or change in the lives of those it serves. Semiotics and discourse analysis are supposed to be the main methodological tools in the culturally-turned Pschology research.